2012
DOI: 10.1002/hipo.22038
|View full text |Cite
|
Sign up to set email alerts
|

Modulation by pregnenolone sulfate of filtering properties in the hippocampal trisynaptic circuit

Abstract: Short-term synaptic plasticity alters synaptic efficacy on a timescale that is relevant to encoding information in spike trains. The dynamics of this plasticity, combined with that of the feedback and feedforward contributions of local interneurons, impose frequency-dependent properties on neuronal networks with implications for nervous system function. The trisynaptic network of the hippocampus is especially well suited to selectively filter components of frequency-dependent signals that are transmitted from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 56 publications
1
6
0
Order By: Relevance
“…Figuring out the computations of the DG is equivalent to reverse-engineering the transfer function defining the DG filter. Some have suggested that the DG is a low-pass [22, 76] or a ~10 Hz band-pass filter [21]. Our results confirm that the output frequency of GCs is constrained in a narrow band ( Fig 5B ) and go one step further by providing the first demonstration that the filtering properties of the DG allow it to perform different computations including pattern separation in response to complex naturalistic inputs ( Fig 6 ).…”
Section: Discussionsupporting
confidence: 80%
“…Figuring out the computations of the DG is equivalent to reverse-engineering the transfer function defining the DG filter. Some have suggested that the DG is a low-pass [22, 76] or a ~10 Hz band-pass filter [21]. Our results confirm that the output frequency of GCs is constrained in a narrow band ( Fig 5B ) and go one step further by providing the first demonstration that the filtering properties of the DG allow it to perform different computations including pattern separation in response to complex naturalistic inputs ( Fig 6 ).…”
Section: Discussionsupporting
confidence: 80%
“…In this neuronal network, the trisynaptic circuit of the hippocampal formation, the flow of impulses comes from the entorhinal cortex (EC) and propagates through the DG, CA3 and CA1 regions (Kempermann, 2011; Scullin and Partridge, 2012; Wojtowicz, 2012). This propagation pattern leads to the formation of a loop, with the impulses being transmitted back to the EC.…”
Section: The Hippocampus and The Olfactoy Bulb: General Anatomy Anmentioning
confidence: 99%
“…We have previously demonstrated low-pass filter characteristics of layer V glutamatergic inputs to MSNs in the striatum (Jelinek and Partridge, 2012) and provided evidence that GABAergic feedback mechanisms underlie these characteristics. We have also previously shown differential filtering characteristics within the CA3, CA1, and dentate gyrus of the hippocampus (Scullin and Partridge, 2012), indicating that filter properties are a local property of specific brain regions. If this low-pass filtering and synaptic plasticity are a characteristic feature of the cortico-striatal circuitry, it is an interesting and important question to examine how these phenomena may interact.…”
Section: Introductionmentioning
confidence: 60%